An Ethnic Relations between Immigrant-based Groups in the Light of Florian Znaniecki’s Theory. (Ethnic Relations as a Type of Social Relations: Case Study on Polish-Ukrainian Relations in Diaspora Situation) - Fiń, Anna (Italian Sociological Review, 2020)
This presentation is related to three aspects of the sociological theory of Florian Znaniecki and William Thomas: the concept of ethnic relations and immigrants attitudes in diaspora situation as well as the concept of recreate and building of an ethnic community. The main problem tackled in the paper can be narrowed down to the question: whether and how is the system of social relationships between different ethnic groups transferred into a migration situation? Relations between Polish and Ukrainian immigrants will be use as an example. What guides this paper is trading these realtions in the sphere of everyday life in one of New York’s Lower Manhattan neighborhoods – East Village, where Polish and Ukrainian ethnic community in New York City formed in the second half of the 19th century. The text portrays the community eastablished by the immigrants, and especially its past and the character of Polish-Ukrainian neighborhood, which, as it turns out, resembles Polish-Ukrainian in the European borderland. In the analysis particular attention will be focus on microsocial determinants of mutual relationships as well as on the various elements of interethnic relations, including: spheres of cooperation, conflict areas, daily interactions, ethnic distance, mutual perceptions, etc. The text will give a short outline of the process of shaping and functioning of the ethnic community, its character, as well as the processes of changes of the ethnic community.